Paternalistic Intervention The Moral Bounds on Benevolence. - Vandeveer, Donald (Princeton : Princeton University Press, 2014)
Donald VanDeVeer probes the moral complexities of the question: under what conditions is it permissible to intervene invasively in the lives of competent persons--for example, by deception, force, or coercive threat--for their own good? In a work with broad significance for law, public policy, professional-client relations, and private interactions, he presents a theory of an autonomy-respecting"" paternalism. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the.
Cover; Contents; 1. The Nature and Scope of Paternalism; 2. Appeals to Consent; 3. Appeals to Doing Good; 4. The Doctrine of Informed Consent; 5. Death, Sex, Odysseus and theSirens; 6. Paternalistic Limits on Risk Taking; 7. Our Dealings with Incompetents; 8. Overview,Reservations, and Implications
Description based upon print version of record.
Keywords: Benevolence; Paternalism -- Moral and ethical aspects; Respect for persons; Respect for persons; Paternalism -- Moral and ethical aspects; Benevolence; PHILOSOPHY / Ethics & Moral Philosophy; PHILOSOPHY / Social; Electronic books